Forest succession, soil carbon accumulation, and rapid nitrogen storage in poorly remineralized soil organic matter. Issue 10 (1st October 2014) - Lewis, David Bruce; Castellano, Michael J.; Kaye, Jason P.
Abstract : Substantial nitrogen (N) retention by temperate terrestrial ecosystems results from the rapid storage of newly deposited N in stable soil organic matter. Yet, we poorly understand the ecosystem properties that regulate the kinetics of this process. We applied mineral 15 N to temperate hardwood forest soils to test the hypothesis that N stabilization is faster owing to greater stocks of soil carbon (C) in late‐successional than in young forests. Within 26 minutes of addition, about 30% of tracer N was stored in stable form in organic‐horizon soil with a median residence time of >29 years. About 5–10% of tracer N was stored in a soluble organic form. An additional 30% of tracer N was recovered within hours from organic‐horizon soils in a remineralizable (labile) form, apparently derived from microbial biomass. Over the following year, tracer N storage in stable and soluble organic pools remained constant while recovery from labile and microbial pools declined. Tracer storage was greater in older forests with larger soil C pools, supporting our hypothesis that the accumulation of soil C with forest succession promotes ecosystem N retention. Rapid storage of stable soil N in the O horizon may create a source for chronic dissolved organic N losses from watersheds.